Analisis Penerapan Program Keselamatan Kerja Dalam Usaha Meningkatkan Produktivitas Kerja Dengan Pendekatan Fault Tree Analysis - Syifa Avrianda (JEMA: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This research aims to increase work productivity at PTPN II Seberang Sawit PKS Operations by analyzing work accident data using the fault tree analysis method. This research was conducted in the first quarter of 2024 (January-March) by directly observing performance conditions and referring to related literature, with the aim of identifying the causes of accidents and finding solutions to improve work safety. In this research, the author measures the level of work safety by looking at how often accidents occur and how much work time is lost due to accidents. The results show that the more accidents, the lower the work productivity.